Respuesta :

Answer:

  3x -y = 6

Step-by-step explanation:

When the equation of a line is given in the form ax+by=c, the perpendicular line through point (h, k) will be ...

  bx -ay = bh -ak

Here, we have a=1, b=3, h=1, k=-3, so the line is ...

  3x -y = 3(1) -(1(-3))

  3x -y = 6

Ver imagen sqdancefan

Answer:

  1. -3x +y = -6 or y = 3x -6

Step-by-step explanation:

Arrange values into slope intercept form ; y=mx+b

[tex]x +3y = 21\\3y = -x +21\\3y/3 = -x/3 +21/3\\\\y = -1/3 x + 7[/tex]

[tex](1, -3) =(x ,y)\\\\y =-\frac{1}{3}x + 7\\\\m = -\frac{1}{3} \\\\m_2=-1/m_1\\\\m_2 =\frac{-1}{-\frac{1}{3} } \\\\m_2=3\\[/tex]

Arrange values into slope - intercept form and solve for b

[tex]-3 = 3(1 )+ b\\-3 = 3 +b\\-3-3=b\\-6 =b\\\\b=-6\\m =3[/tex]

Substitute new values into slope intercept form

[tex]y = 3x -6[/tex]

Arrange in standard form

[tex]-3x +y = -6[/tex]

ACCESS MORE